Representation of Thermal Information in the Antennal Lobe of Leaf-Cutting Ants - Ruchty, Markus; Helmchen, Fritjof; Wehner, Rüdiger; Kleineidam, Christoph J. (Frontiers in Behavioral Neuroscience, 2010)
Insects are equipped with various types of antennal sensilla, which house thermosensitive neurons adapted to receive different parameters of the thermal environment for a variety of temperature-guided behaviors. In the leaf-cutting ant Atta vollenweideri, the physiology and the morphology of the thermosensitive sensillum coeloconicum (Sc) has been thoroughly investigated. However, the central projections of its receptor neurons are unknown. Here we selectively stained the three neurons found in single Sc and tracked their axons into the brain of Atta vollenweideri workers. Each of the three axons terminates in a single glomerulus of the antennal lobe (Sc-glomeruli). Two of the innervated glomeruli are adjacent to each other and are located laterally, while the third one is clearly separated and located medially in the antennal lobe. Using two-photon Ca2+ imaging of antennal lobe projection neurons, we studied where in the antennal lobe thermal information is represented. In the 11 investigated antennal lobes, we found up to 10 different glomeruli in a single specimen responding to temperature stimulation. Both, warm- and cold-sensitive glomeruli could be identified. The thermosensitive glomeruli were mainly located in the medial part of the antennal lobe. Based on the general representation of thermal information in the antennal lobe and functional data on the Sc-glomeruli we conclude that temperature stimuli received by Sc are processed in the medial of the three target glomeruli. The present study reveals an important role of the antennal lobe in temperature processing and links a specific thermosensitive neuron to its central target glomerulus.